The context of economic insecurity and its relation to violence and risk factors for HIV among female sex workers in Andhra Pradesh, India. - Reed, Elizabeth; Gupta, Jhumka; Biradavolu, Monica; Devireddy, Vasavi; Blankenship, Kim M (Public health reports (Washington, D.C. : 1974), 2010)
We examined the context of economic insecurity and debt among female sex workers (FSWs), how this context varies among FSWs, and its association with experiences of violence and sexual risk factors for human immunodeficiency virus (HIV).
Keywords: Adolescent; Adult; Female; HIV Infections; Humans; India; Interviews as Topic; Logistic Models; Male; Odds Ratio; Poverty; Prostitution; Risk Factors; Spouse Abuse; Unsafe Sex; Violence; Young Adult